2002
DOI: 10.1038/sj.mp.4001085
|View full text |Cite
|
Sign up to set email alerts
|

Association between the dopamine transporter gene and posttraumatic stress disorder

Abstract: Posttraumatic stress disorder (PTSD) is a chronic anxiety disorder that follows exposure to extreme events. A large twin study of Vietnam veterans had demonstrated a significant genetic contribution to chronic PTSD upon exposure to combat.1,2 The underlying genes, however, have not been described. Given previous findings of abnormal dopamine (DA) function in PTSD, and given the putative effect of dopamine neurotransmission in shaping the responses to stress in animals, this study examined the association of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(103 citation statements)
references
References 27 publications
3
94
2
3
Order By: Relevance
“…We also compiled a list of genes that have been reported in the literature to be significantly associated with PTSD, either showing a main effect for the genetic marker, and/or a significant GxE interaction (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013). Since most studies were performed in subjects of either European or African descent, we used these specific ancestry groups for comparison with MRS. We found that most of the 25 candidate genes showed nominally significant associations in MRS for at least one of the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also compiled a list of genes that have been reported in the literature to be significantly associated with PTSD, either showing a main effect for the genetic marker, and/or a significant GxE interaction (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013). Since most studies were performed in subjects of either European or African descent, we used these specific ancestry groups for comparison with MRS. We found that most of the 25 candidate genes showed nominally significant associations in MRS for at least one of the SNPs tested.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has focused on: (1) the hypothalamic-pituitary-adrenal (HPA) axis, (2) the ascending brainstem locus coeruleus noradrenergic system, and (3) the limbic amygdalar frontal pathway mediating fear processing. Among the over 25 PTSD candidate genes currently reported (Amstadter et al, 2009(Amstadter et al, , 2011Binder et al, 2008;Boscarino et al, 2011;Cao et al, 2013;Comings et al, 1996;Dragan and Oniszczenko, 2009;Gillespie et al, 2013;Goenjian et al, 2012;Grabe et al, 2009;Guffanti et al, 2013;Hauer et al, 2011;Kolassa et al, 2010;Logue et al, 2013a,b;Lyons et al, 2013;Mellman et al, 2009;Nelson et al, 2009;Ressler et al, 2011;Segman et al, 2002;Solovieff et al, 2014;Voisey et al, 2010;Wilker et al, 2013;Xie et al, 2013), promising findings include associations of PTSD symptoms with the serotonin transporter gene (SERT, SLC6A4) (Xie et al, 2009), which is linked to depression and anxiety disorders, as well as differential acquisition of conditioned fear and increased amygdala excitability in humans. In addition, FKBP5, a co-chaperone of the glucocorticoid receptor involved in the HPA axis, has a significant interaction with severity of child abuse in the prediction of adult PTSD symptoms, indicating a gene by environment (GxE) interaction (Binder et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These include polymorphisms or expression of BDNF (Krishnan et al, 2007), GABRA2 (Nelson et al, 2009), 5-HT1A receptors, dopamine or serotonin transporters (Segman et al, 2002;Kilpatrick et al, 2007;Stein et al, 2009;Wald et al, 2013), catechol-O-methyl transferase (COMT; Jabbi et al, 2007;Kolassa et al, 2010), glucocorticoid receptors and factors that modulate them such as FK506-binding protein (FKBP5;Binder et al, 2008;Derijk and de Kloet, 2008;McGowan et al, 2009;Sarapas et al, 2011), and methylation of corticotrophin-releasing factor (CRF) receptor DNA (Elliott et al, 2010). Several genetically distinct rodent lines are differentially resistant/vulnerable to the effects of stress (Razzoli et al, 2011;Savignac et al, 2011;Camp et al, 2012;Fuchsl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serotonin transporter function was demonstrated as being influenced by BDNF in a 5-HTTLPR genotype-dependent fashion (Mössner et al, 2000). The DAT VNTR has been less intensively investigated, although it had been reported previously as being associated with post-traumatic stress disorder (PTSD) (Segman et al, 2002). It seems, therefore, reasonable to examine potential interactive influences of these polymorphisms and BDNF on individual differences in Neuroticism and related personality traits.…”
Section: Introductionmentioning
confidence: 99%